Career break or broken career? : mothers' experiences of returning to paid work : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy at School of Sociology, Social Policy and Social Work, Massey University, Palmerston North, New Zealand - Ang, Ee Kheng (Massey University, 2007)
Servicemen returning from two World Wars were granted assistance in finding work, retraining and other benefits in recognition of the sacrifices they had made. Yet mothers' returning to work after time out bearing and raising children are reliant on a booming economy to obtain even limited entry to the labour market, and the work obtained is very often inferior to the jobs held by women before becoming mothers. Currently due to lower fertility rates and the ageing populations of the world's richer nations, a shortage of working-age people is predicted to continue into at least the middle of the twenty-first century. To overcome this shortfall, the Organisation for Economic Cooperation and Development (OECD) advises its member states to assist mothers to return to paid work sooner. Most OECD nations are complying, with varying degrees of success. Some policy frameworks make this goal more easily attainable than others. Mothers in liberal welfare states often return to paid work later than they might otherwise prefer. Many returners are overqualified for the work they are doing. While there appears to be relatively few barriers to re-entry, the choice of re-entry occupations are limited and returners are predominantly offered low status jobs with no career opportunities at the back of the job queue and gender queue. Mothers who interrupt their careers by taking a career break for childbearing and rearing generally face downward occupational mobility and loss of lifetime incomes. This thesis assesses the experiences of mothers who return to employment in one liberal nation, New Zealand. It applies Esping-Andersen's three models of welfare states and Reskin and Roos' gender queues model to the situation of returners. The study investigates the precise nature of the obstacles and processes encountered by a number of mothers attempting to resume a career. It argues that social policies matter: returners in countries where state intervention is more widespread and where there is universal, extensive and generous social provision and support for working mothers are economically better off. The research methods include in-depth interviews and a focus group with mothers, a mail questionnaire and interviews with employers, and a study of recent and current New Zealand and overseas government policies to assist working parents. The findings of this thesis are that regardless of skill levels, New Zealand returners are consigned to low status occupations where they are not fully integrated into the 'normal' full-time workforce with career opportunities. These mothers generally suffer more than one episode of returning to the back of the queue. They also earn less (weekly and annually) than mothers who do not take career breaks. The study identifies social policy frameworks and employers' policies and practices as factors contributing to the processes whereby returners are relegated to the back of the queue. Although New Zealand has recently brought in policies to assist mothers to return to paid work these initiatives have not addressed the processes that currently confine returners in low status, part-time employment. Policies similar to those created to specifically target the needs of ex-servicemen would go a long toward assisting mothers to access higher status and better-paid jobs at the head of the queue. The thesis concludes with policy recommendations to facilitate mothers' integration into such jobs.
Keywords: Mothers; Employment; Working mothers; Discrimination in employment; Sex discrimination in employment; Work and family; Government policy; New Zealand; Fields of Research::370000 Studies in Human Society::370200 Social Work::370203 Social policy